Consistent prokaryotic successional dynamics across contrasting phytoplankton blooms - Gómez‐Letona, Markel; Arístegui, Javier; Riebesell, Ulf; Sebastián, Marta (Limnology and Oceanography, 2025)
Heterotrophic prokaryotes play a vital role in organic matter cycling in the ocean and have been observed to undergo substrate‐controlled successions during phytoplankton blooms. However, there is limited understanding of the succession patterns during blooms triggered by upwelling events of different characteristics. Here we simulated eight upwelling scenarios of varying intensity and duration (single vs. recurring pulses) by adding nutrient‐rich mesopelagic waters into large‐scale mesocosms containing oligotrophic surface waters from the subtropical North Atlantic. Over a monitoring period of nearly 6 weeks, we observed that phytoplankton blooms displayed diverging outcomes depending on the upwelling mode: treatments with single upwelling pulses presented a unique, short‐lived bloom, whereas recurring upwelling resulted in blooms that were sustained over time. Prokaryotic abundances were positively related to upwelling intensity and presented three similar abundance cycles in all treatments, whereas heterotrophic activity differed between the two upwelling modes. The successional dynamics of free‐living and particle‐associated communities were consistent regardless of upwelling intensity and mode, with four or five prokaryotic assemblages sequentially proliferating during the experiment. Yet, some differences were observed in the taxa that formed the assemblages in both upwelling modes. Together, our results suggest that, despite differences in activity, prokaryotes seemed to be more influenced by processes taking place within the community than by phytoplankton bloom patterns, with similar succession dynamics even under widely distinct blooms. These findings can help advance our understanding on prokaryotic ecology and its relation to organic matter cycling across different upwelling scenarios.